2009
DOI: 10.1097/nen.0b013e3181a52a7f
|View full text |Cite
|
Sign up to set email alerts
|

Endocan Expression and Localization in Human Glioblastomas

Abstract: Glioblastomas (GBMs) are highly malignant tumors characterized by microvascular proliferation and the pseudopalisading pattern of necrosis. Investigations have, therefore, focused on vascular and endothelial cell biology in GBM. Endocan, also called endothelial cell-specific molecule-1, is a proteoglycan that is secreted by endothelial cells and upregulated by proangiogenic factors. We found that endocan is not only expressed in vitro by endothelial cells but also in the T98G and U118MG human GBM cell lines. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
131
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 37 publications
5
131
3
1
Order By: Relevance
“…Endocan is a secreted proteoglycan (12) that is upregulated by growth factors and chemokines in vitro (13,14) and on tumor vasculature in several types of cancer (15)(16)(17), with diverse suggested biologic roles (18). Using quantitative reverse-transcription PCR (qRT-PCR) and immunohistochemistry, we found that endocan was strongly upregulated on tumor vascular endothelium and that its expression correlated with the invasiveness of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Endocan is a secreted proteoglycan (12) that is upregulated by growth factors and chemokines in vitro (13,14) and on tumor vasculature in several types of cancer (15)(16)(17), with diverse suggested biologic roles (18). Using quantitative reverse-transcription PCR (qRT-PCR) and immunohistochemistry, we found that endocan was strongly upregulated on tumor vascular endothelium and that its expression correlated with the invasiveness of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact regulatory mechanism of endocan production is not well established, recent studies suggest that a number of signaling pathways and bioactive mediators are involved. The expression of endocan is upregulated by VEGF-A, VEGF-C, tumor necrosis factor-α, and transforming growth factor-β1 (Lassalle et al 1996;Rennel et al 2007;Maurage et al 2009;Delehedde et al 2013). Because of these relations between endocan and VEGF, we compared the diagnostic efficiencies of VEGF and endocan with carcinoembryonic antigen (the tumor marker that currently provides the best diagnostic accuracy (Shi et al 2008) and CYFRA.…”
Section: Discussionmentioning
confidence: 99%
“…This activates hypoxia-inducible factor signaling, resulting in the secretion of VEGF from both tumor cells and tumor-associated stromal cells in an attempt to ensure that the tumor's oxygen requirements are met (Maurage et al 2009). The vascular growth-promoting action of VEGF is mediated by endocan.…”
Section: Introductionmentioning
confidence: 99%
“…In high-grade gliomas also called glioblastomas (n=42), endocan immunoreactivity has always been detected in endothelial cells within the tumor and those at the margins of the tumors (Maurage et al, 2009). Endocan was never detected in the cerebral cortex distant from the tumors and endothelial cells are mostly all endocan negative in low-grade gliomas (grade I and grade II).…”
Section: Endocan Overexpression In Cancermentioning
confidence: 99%
“…Endocan was never detected in the cerebral cortex distant from the tumors and endothelial cells are mostly all endocan negative in low-grade gliomas (grade I and grade II). Therefore in brain tumors, endocan expression is associated with a higher grade and with the abnormal vasculature reflecting neoangiogenesis in glioblastomas (Maurage et al, 2009). …”
Section: Endocan Overexpression In Cancermentioning
confidence: 99%